A VECM Approach Towards the Effect of Bank Credit on Economic Growth: Empirical Evidence for Nigeria - Samson Olusegun Akinwale; Oluwabusayo Temitope Obagunwa (European Scientific Journal, ESJ, 2019)
Despite policy reforms to enhance the performance of commercial banks and their contributions to economic growth, little has been achieved in the economy. This is due to the country still experiencing low domestic investment, high unemployment rate, and escalating poverty resulting from lack of adequate credits required for investment and production activities in the economy. The study investigated the effect of bank credit on economic growth in Nigeria by using secondary data from Central Bank of Nigeria (CBN) Statistical Bulletin covering the period of 1981 to 2017. The study employed Augmented Dickey – Fuller (ADF), Johansen C-integration, Error Correction Model, and Pairwise Granger Causality Techniques. The result ADF indicated that credit to manufacturing sector (CMS), agricultural sector (ACS), general commerce (CGC), and real gross domestic product (RGDP) were stationary at first difference order of integration. On the other hand, the Johansen Co-integration test revealed that there is a long-run relationship among the variables. The result of the Error Correction Model revealed that CMS and ACS simulate RGPS while CGC negatively influenced economic growth in Nigeria. Also, CMS and ACS granger did not cause RGDP, but CGS granger caused RGDP. The study concluded that bank credit to different sectors of the economy plays significant role in promoting economic growth in Nigeria. The study recommended that banks should ensure more credits flow to the manufacturing sector and agricultural sector in order to ensure bidirectional relationship between bank sectoral credit and economic growth.